Progress in Nano-Electro-Optics VII Chemical, Biological, and Nanophotonic Technologies for Nano-Optical Devices and Systems - Ohtsu, Motoichi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book focuses on chemical and nanophotonic technology to be used to develop novel nano-optical devices and systems. It begins with temperature- and photo-induced phase transition of ferromagnetic materials. Further topics include: energy transfer in artificial photosynthesis, homoepitaxial multiple quantum wells in ZnO, near-field photochemical etching and nanophotonic devices based on a nonadiabatic process and optical near-field energy transfer, respectively and polarization control in the optical near-field for optical information security. Taken as a whole, this overview will be a valuable resource for engineers and scientists working in the field of nano-electro-optics.
Photo-Induced Phase Transition in RbMnFe Prussian Blue Analog-Based Magnet -- Photoinduced Energy Transfer in Artificial Photosynthetic Systems -- Electro-Magneto-Optics in Polarity-Controlled Quantum Structures on ZnO -- Nonadiabatic Near-Field Optical Polishing and Energy Transfers in Spherical Quantum Dots -- Shape-Engineered Nanostructures for Polarization Control in Optical Near- and Far-Fields.
Keywords: Nanotechnology; Materials Science; Nanotechnology; Optics, Optoelectronics, Plasmonics and Optical Devices; Solid State Physics; Spectroscopy and Microscopy